ANALISIS HUKUM PIDANA ISLAM TERHADAP PUTUSAN BEBAS (VRIJSPRAAK ) (Studi Putusan Nomor 454/PID.B/2024/PN.SBY) - Kasmarani, Yuli (Universitas Islam Negeri Sumatera Utara, 2024)
This research aims to analyze acquittal decisions (Vrijspraak) (study decision Number 454/Pid.B/2024/PN.Sby) from the perspective of Islamic Criminal Law and answer the question of whether a judge may decide a case based on his own knowledge. Considering the large number of perpetrators of criminal acts who were acquitted by the judge because based on the results of the trial it was not legally proven and convinced the judge that the defendant had actually committed the crime. This research is normative juridical research sourced from secondary data, collected based on literature studies and then the data is processed and analyzed descriptively qualitatively. The results of the research conclude that from the perspective of Islamic criminal law, the actions of the defendant Gregorius Ronald Tanur in decision Number 454/Pid.B/2024/PN.Sby have fulfilled the elements of semi-intentional murder and the sanction is in the form of diyat (a fine that must be paid to the victim's family either in the form of camels, gold, silver, wheat, goats, and jewelry, according to the predetermined diyat levels) if the judge has doubts about imposing a diyat sentence, the judge can replace the diyat sentence with a ta'zir punishment, namely a punishment that is repressive, preventive, and educative. Judges' decisions based on their own knowledge are completely unacceptable nowadays, because many of today's judges are irresponsible.Keyword: Islamic Criminal Law, acquittal decisions, Vrijspraak